Teachers' perception and challenges in integrating islamic values (islamic integration) in natural and social sciences learning at MI Plus Al Falah Banjarmasin - Jumiati Jumiati; Tutus Rani Arifa; Abdurrahim Abdurrahim (Institute of Computer Science (IOCS), 2026)
This study aims to analyze teachers' perceptions and identify challenges faced in integrating Islamic values (Islamic Integration) into Natural and Social Sciences (IPAS) learning at MI Plus Al Falah Banjarmasin. The integration of Islamic values in IPAS learning is a crucial issue in the implementation of the Independent Curriculum because it is not only oriented towards mastery of knowledge, but also towards character building and spiritual strengthening of students. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, open-ended surveys, and literature studies. Research informants were selected through purposive sampling, namely teachers involved in IPAS learning and the implementation of the Independent Curriculum and the school principal. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers have a very positive perception of the implementation of Islamic Integration in science and science learning. Teachers believe that the integration of Islamic values can improve students' understanding of the relationship between science and Islamic teachings, while strengthening their religious character. The implementation of integration is carried out by linking science and science material with relevant verses of the Quran and hadith, especially on material related to living things and natural phenomena. However, the study also found several major challenges, namely teachers' limited knowledge of the concept of science and Islam integration, difficulty in finding appropriate evidence for science and science material, and the unavailability of teaching modules and learning tools based on Islamic Integration. On the other hand, the support of madrasah principals and the flexibility of the Independent Curriculum are supporting factors that strengthen the implementation of this integration. This study concludes that the successful implementation of Islamic Integration in science and education learning is influenced not only by positive teacher perceptions, but also by the availability of learning tools, professional training, and ongoing institutional support. Therefore, programs to strengthen teacher competency, develop integrated teaching modules, and develop more systematic madrasah policies to support Islamic values-based science and education learning are needed.